2010
DOI: 10.1577/a09-044.1
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Feed Efficiency of Channel × Blue Catfish Hybrids Stocked at Various Densities and Fed Once or Twice Daily in Ponds

Abstract: Two experiments were conducted to evaluate the effects of stocking density and feeding frequency on the growth, net yield, and feed conversion of hybrid catfish (female channel catfish Ictalurus punctatus × male blue catfish I. furcatus). In experiment 1, hybrid catfish fingerlings with a mean initial weight of 65 g were stocked into ten 0.4‐ha earthen ponds at a density of 12,355 fish/ha. In experiment 2, hybrid catfish fingerlings with the same mean initial weight as in experiment 1 were stocked into twenty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
(3 reference statements)
3
4
0
Order By: Relevance
“…Direct comparison of hybrid catfish production traits reported in this study with other reports in the literature is difficult due to differences in study design (e.g., duration, cropping system, management practices), but the values for harvest weight (∼0.80 kg), survival (>93%), FCR (∼2.0), and net production (6,135-16,492 kg/ha) were good and compare favorably with other reports for production of hybrid catfish in single-batch production (Dunham et al 1990;Bosworth et al 2004;Green and Rawles 2010;Li et al 2010). Carcass and fillet yield reported in the current study were lower than values reported for hybrid catfish by Bosworth et al (2004), Li et al (2007), Jing et al (2008, and Bosworth (2012), but similar to those reported by Li et al (2012).…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Direct comparison of hybrid catfish production traits reported in this study with other reports in the literature is difficult due to differences in study design (e.g., duration, cropping system, management practices), but the values for harvest weight (∼0.80 kg), survival (>93%), FCR (∼2.0), and net production (6,135-16,492 kg/ha) were good and compare favorably with other reports for production of hybrid catfish in single-batch production (Dunham et al 1990;Bosworth et al 2004;Green and Rawles 2010;Li et al 2010). Carcass and fillet yield reported in the current study were lower than values reported for hybrid catfish by Bosworth et al (2004), Li et al (2007), Jing et al (2008, and Bosworth (2012), but similar to those reported by Li et al (2012).…”
Section: Discussionsupporting
confidence: 63%
“…Ammonia and nitrite can negatively affect growth and survival of catfish in tank studies (Colt and Tchobanoglous 1978;Colt et al 1981), but sublethal effects of nitrogenous waste products on catfish production in earthen ponds are more difficult to demonstrate consistently (Hargreaves and Tomasso 2004). Li et al (2010) observed an 18% decrease in hybrid catfish harvest weight when density increased, but no difference in ammonia nitrogen at different densities. Torrans (2008) and Green and Rawles (2011) reported growth suppression of Channel Catfish raised under low DO compared with high DO conditions, but no relationship between growth and ammonia levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With growing interest in hybrid catfish production, knowledge of optimum feeding rates and frequencies would assist hybrid growers in better management of hybrid production, and thus improve production efficiency and profit. Li et al (2010) evaluated feeding hybrid catfish once or twice daily during food fish grow out and found that feeding once daily provided satisfactory growth. There was no benefit to feeding hybrid catfish twice daily.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%